Global and Malaysian perspectives on mental health and digital interventions (2020–2025): A narrative review - Abdullah, Rosmiza Wahida; Abd Samad, Rosleen (Research and Scientific Innovation Society, 2025)
Since 2020, mental health concerns have become more severe worldwide, driven by the COVID-19 pandemic, economic instability, and social inequalities. During this period, digital and remote mental health services expanded, offering alternatives and complements to in-person care. This narrative review synthesizes global evidence on mental health trends from 2020 to 2025 and examines how Malaysia has responded, with a focus on digital and remote solutions. It brings together findings on mental disorders, vulnerable populations, suicide and self-harm, and the growing role of loneliness and social isolation, alongside Malaysian evidence on digital initiatives and implementation challenges. Overall, evidence indicates that depression and anxiety increased in the early stages of the pandemic, although patterns varied across regions and groups; healthcare workers, university students, children and adolescents. Children and adults experienced a disproportionate burden, while loneliness and social isolation emerged as important independent risk factors. Digital and remote interventions, including telepsychiatry, mobile applications, and web-based programs, generally produced small to moderate benefits and were well accepted, yet access remained uneven. Malaysian trials of smartphone- and text-based coaching tools, WhatsApp-delivered community support, and online suicide prevention initiatives demonstrated feasibility and promise but also highlighted barriers related to digital literacy, language, regulation, and infrastructure. Governmental and private-sector initiatives, such as telepsychiatry expansion, digital health platforms, and AI-enabled tools, signal a shift towards digital mental health. The review concludes that a coordinated national strategy that integrates community-based care, promotes digital equity, and is supported by robust governance is needed to realize the potential of digital and remote mental health services in Malaysia.